Symptomatic congenital cytomegalovirus infection in two consecutive sisters. Issue 5 (November 1993) - Nigro, G; Clerico, A; Mondaini, C
Abstract : The occurrence of symptomatic congenital cytomegalovirus (CMV) infection in two consecutive sisters is reported. The first sibling showed hepatosplenomegaly with slight hyperbilirubinaemia and abnormal liver function tests, right inguinal hernia, and peripheral lymphoedema. Her sister, the product of an uneventful pregnancy showing no signs of CMV reactivation, had life threatening CMV disease, including microcephaly, hepatitis with high serum bilirubin concentrations, and thrombocytopenic purpura.